Fibrous Extracellular Spheroids in an Endoscopic Ultrasound-Guided Pancreatic Fine Needle Aspiration Correlating to a Gyriform Pancreatic Endocrine Tumor with a Unique Cobblestone Pavement Growth Pattern. (15th October 2019) - Marotta, Alessandro; Reynolds, Jordan P.; Plesec, Thomas P.; Rene Rodriguez, E.; Jang, Sunguk N.; Policarpio-Nicolas, Maria Luisa C.; Springer, Bridgette; Sturgis, Charles D.
Abstract : Pancreatic neuroendocrine neoplasms (PanNENs) are uncommon tumors. Fine needle aspiration (FNA) samples from PanNENs are typically of high cellularity and lack necrosis. In cytology slides from these tumors, dyscohesive cells are usually reported with variably round to oval to plasmacytoid forms exhibiting coarsely granular chromatin and showing immunoreactivity for synaptophysin. We present an unusual, and to our knowledge not previously described, example of an FNA of a PanNEN with large extracellular fibrous spheroids containing intrinsic fibroblasts and rimmed by small to intermediate sized neoplastic epithelial cells with high nuclear cytoplasmic ratios. The cytomorphology of the PanNEN in this case was in some ways reminiscent of that expected in adenoid cystic carcinomas of the salivary glands that most often contain large extracellular globules of basement membrane material and a somewhat biphasic population of lesional cells. The cytomorphology in this case was found to correlate well with the resection specimen histomorphology of an exaggerated gyriform pattern of growth resulting in a unique cobblestone-pavement like microscopic appearance. Knowledge of this potential cytomorphology will aid the cytology community through recognition and reporting of this previously undescribed pattern in an uncommon disease.